Analysing quantitative data : variable-based and case-based appro aches to non-experimental datasets - Kent, Raymond A. (Los Angeles : Sage, 2015)
"This innovative book provides a fresh take on quantitative data ana lysis within the social sciences. Using multidisciplinary non-experimen tal datasets it demonstrates that data analysis is really an active dia logue between ideas and evidence, between research objectives and data in a dataset." --
Part I. Quantitative data : structure, preparation and analysis appr oaches : 1. Data structure -- 2. Data preparation -- 3. Approaches to d ata analysis -- part II. Variable-based analyses : 4. Univariate analys is -- 5. Bivariate analysis -- 6. Multivariate analysis -- part III. Ca se-based analyses : 7. Set-theoretic methods and configurational data a nalysis -- 8. Cluster and discriminant analysis -- part IV. Comparing a nd communicating results : 9. Comparing and mixing methods -- 10. Evalu ating hypotheses, explaining and communicating results.
Includes bibliographical references (p. 343-346) and index.
Keywords: Quantitative research -- Methodology; Social sciences -- Research -- Methodology; Qualitative research